Islam Observed: The Case of Contemporary Malaysia - Laurent Metzger (Studia Islamika, 1998)
The phenomenon of the rise of Islam in Malaysia does not attract much attention of observers when compared with the same phenomenon in the countries of the Middle East, North Africa, Central or South Asia. This paper attempted to review comprehensively the development of Islam in Malaysia since obtaining its independence from Britain in August 1957.DOI: 10.15408/sdi.v5i2.753